Small-Sided Games are More Enjoyable Than High-Intensity Interval Training of Similar Exercise Intensity in Soccer - Selmi O; Ouergui I; Levitt DE; Nikolaidis PT; Knechtle B; Bouassida A (Dove Medical Press, 2020)
Okba Selmi,1,2 Ibrahim Ouergui,1 Danielle E Levitt,3,4 Pantelis T Nikolaidis,5 Beat Knechtle,6 Anissa Bouassida1 1Research Unit, Sportive Performance and Physical Rehabilitation, High Institute of Sports and Physical Education of Kef, University of Jendouba, Kef, Tunisia; 2High Institute of Sports and Physical Education, Ksar Said, University of Manouba, Tunis, Tunisia; 3Applied Physiology Laboratory, University of North Texas, Denton, TX, USA; 4Department of Physiology, School of Medicine, Louisiana State University Health Sciences Center New Orleans, New Orleans, LA, USA; 5Exercise Physiology Laboratory, Nikaia, Greece; 6Institute of Primary Care, University of Zurich, Zurich, SwitzerlandCorrespondence: Beat KnechtleInstitute of Primary Care, University of Zurich Medbase St. Gallen Am Vadianplatz, Vadianstrasse 26, St. Gallen 9001, SwitzerlandTel +41 71 226 93 00Fax +41 71 226 93 01Email beat.knechtle@hispeed.chIntroduction: High-intensity interval training (HIIT) and small-sided games (SSG) have been applied and tested for athletes in order to enhance the soccer performance. For this reason, this experimental study aimed to compare the effects of SSGs and HIIT on power, physiological responses and perceived enjoyment.Materials and Methods: Sixteen youth soccer players (age, 17.5± 0.6 years, mean±standard deviation; height, 178.2± 6.4 cm; body mass, 70.4± 5.4 kg; body fat, 10.6± 0.8%) completed one session each of HIIT and SSG on separate days with 1 week between sessions. Each session lasted  25 mins (4x4 mins work with 3 mins of passive recovery in-between). SSGs consisted of 4 versus 4 player games on a 25× 35 m pitch, and HIIT consisted of intermittent 15-s runs at 110% maximal aerobic speed separated by 15 s of passive recovery. Psychological responses following each protocol were assessed using the Physical Activity Enjoyment Scale (PACES). Heart rate (HR) was continuously recorded, rating of perceived exertion (RPE) and lactate concentration [La] were measured after each training session. Lower body muscular power was assessed using the 5-jump test relative to leg length (5JT-relative) before and after each training session, where greater average distance per stride over five sequential jumping strides indicated greater muscular power.Results: HIIT and SSG showed no significant difference in HR, RPE and [La] responses (p=0.70, ES=0.11; p=0.61, ES=0.08 and p=0.38, ES=0.21, respectively). 5JT-relative decreased significantly for SSG and HIIT (p< 0.05, ES=0.50 and p< 0.05, ES=0.40, respectively). PACES score was greater in SSG compared to HIIT (ES=5.35, p< 0.001).Conclusion: HIIT and SSG sessions induced similar physiological responses; however, SSGs induced a higher enjoyment level than HIIT. Coaches could choose between these training modalities according to the objective of their training session, considering the enjoyment-related advantages of SSGs.Keywords: aerobic fitness, psychology, motivation, soccer, athletes